1990
DOI: 10.1002/eji.1830200722
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of major histocompatibility complex class I antigens in T cell activation

Abstract: During the last few years ample evidence has been collected indicating a regulatory role for major histocompatibility complex class I antigens (Ag) in T cell activation. However, due to differential effects (stimulatory and inhibitory) of anti-class I antibodies (Ab) observed under different conditions, no coherent scheme of the mechanism of action of these Ag has emerged. Here, we present evidence that the mode of action of anti-class I Ab depends upon the presence or absence of monocytes/macrophages (M phi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…We previously showed that dilutions of polyclonal anti-ZI^m similar to those used in the present study (1:50-1:100) actually induce significant lymphocyte activation, rather than inhibition, if phorbol esters are added to the cultures [13]. Many monoclonal antibodies to class I antigens will also activate T cells, but ihere is an additional requirement for a second cross-linking antibody before activation occurs [38,39], The precise mechanism of class I antigens in the activation ol'T cells remains unclear. Brams & Claesson [40] showed that mutant lines of thymoma cells thai had lost their class I histocompatibility expression failed to respond to anti-CD3 antibody with the production of IL-2.…”
Section: -mentioning
confidence: 65%
“…We previously showed that dilutions of polyclonal anti-ZI^m similar to those used in the present study (1:50-1:100) actually induce significant lymphocyte activation, rather than inhibition, if phorbol esters are added to the cultures [13]. Many monoclonal antibodies to class I antigens will also activate T cells, but ihere is an additional requirement for a second cross-linking antibody before activation occurs [38,39], The precise mechanism of class I antigens in the activation ol'T cells remains unclear. Brams & Claesson [40] showed that mutant lines of thymoma cells thai had lost their class I histocompatibility expression failed to respond to anti-CD3 antibody with the production of IL-2.…”
Section: -mentioning
confidence: 65%
“…Class I‐specific mAbs have been shown to be capable of inhibiting or promoting lymphocyte proliferation after cross‐linking surface MHC‐I [19–25]. Furthermore, CD3‐ or superantigen‐induced proliferation of T cells can be inhibited by cross‐linking MHC‐I with anti‐MHC‐I antibodies [20,24,26–28].…”
Section: Discussionmentioning
confidence: 99%
“…The MHC‐I‐transmitted signals are dependent on the CD3/TCR‐associated signal‐transducing machinery [19,21,22]. Furthermore, cross‐linking MHC‐I on the cell surface using MHC‐I‐specific antibodies has been shown to either inhibit or promote lymphocyte proliferation [19–25]. For example, cross‐linking MHC‐I on human peripheral CD3 + T cells using immobilized antibodies inhibited CD3‐ or superantigen‐induced proliferation of T cells [20,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained increases in intracellular Ca 2 § can often lead to unresponsiveness in CTL (46); consequendy, MHC class I modification of TCR-CD3 signals may represent another mechanism for the induction of anergy. T cell signaling through the class I molecule does not depend on the MHC cytoplasmic domain (47), but instead requires association of class I protein with other cell surface molecules (48,49). Most studies of MHC class I signal transduction and regulation of CTL effector function have involved the use of antibodies as an MHC cross-linking agent.…”
Section: Discussionmentioning
confidence: 99%